SEROPREVALENCE OF HEPATITIS A VIRUS (HAV) AMONGS THE ACUTE VIRAL HEPATITIS PATIENTS ATTENDING A TERTIARY CARE HOSPITAL. - awar,Dr. G S Karande,DrMahadeo B. Shinde, Dr. Ravindra V. Shinde,Anjali R. Shinde ,Dr.S.T.Mohite,Dr. S. R Patil,Dr. S .K P (International Journal of Advanced Science and Technology, 2020)
Background: Hepatitis A virus (HAV) is a major cause of acute viral hepatitis all over the world. The risk factors associated with the hepatitis A infection is a lack of safe water, and poor sanitation and hygiene .The severity of HAV clinical symptoms in infected cases is related to age. Seroprevalence studies are a reliable method to estimate the susceptibility rate to HAV in populations and can help establish vaccination implementation policies.